Early stimulation: from the play box to the play space - Bahamonde Rodríguez, Teresa (2003)
Using a game box in clinical work, let children express their internal reality into the external realness of the toys. So, the way the children play represents a proyection of their psychic reality. According to Winnicott´s view, the relation mother. Child would be interpreting where early stimulation is based with that individualization process.